Decreased Hippocampal Neuroplasticity and Behavioral Impairment in an Animal Model of Inhalant Abuse - Malloul, Hanaa; Bennis, Mohammed; Bonzano, Sara; Gambarotta, Giovanna; Perroteau, Isabelle; De Marchis, Silvia; Ba-M'hamed, Saadia (Frontiers in Neuroscience, 2018)
Thinners are highly toxic chemicals widely employed as organic solvents in industrial and domestic use. They have psychoactive properties when inhaled, and their chronic abuse as inhalants is associated with severe long-term health effects, including brain damage and cognitive-behavioral alterations. Yet, the sites and mechanisms of action of these compounds on the brain are far from being fully understood. Here, we investigated the consequences of paint thinner inhalation in adult male mice. Depression-like behaviors and an anxiolytic effect were found following repeated exposure in chronic treatments lasting 12 weeks. Both subchronic (6 weeks) and chronic treatments impaired learning and memory functions, while no changes were observed after acute treatment. To investigate possible molecular/structural alterations underlying such behavioral changes, we focused on the hippocampus. Notably, prolonged, but not acute thinner inhalation strongly affected adult neurogenesis in the dentate gyrus (DG), reducing progenitor cell proliferation after chronic treatments and impairing the survival of newborn neurons following both chronic and subchronic treatments. Furthermore, a down-regulation in the expression of BDNF and NMDA receptor subunits as well as a reduction in CREB expression/phosphorylation were found in the hippocampi of chronically treated mice. Our findings demonstrate for the first time significant structural and molecular changes in the adult hippocampus after prolonged paint thinner inhalation, indicating reduced hippocampal neuroplasticity and strongly supporting its implication in the behavioral dysfunctions found in inhalation abuse.